(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
According to the scientific literature, the spread of human parasites in HIV-infected patients is high (10.0-30.0%), external factors, the external environment and social conditions also play a major role in the spread of human parasites. In the course of the investigation, 85 patients with intestinal parasitism (giambliosis and blastocystosis) were diagnosed with HIV-infection and clinical changes were studied. HIV-infected patients with a diagnosis of intestinal parasites (giambliosis, blastocystosis) often experience intoxication, asthenovegetative and dyspeptic syndromes, the frequency of which is 40.9% to 100.0%.